Peningkatan Prestasi Belajar Materi Mengoperasikan Aplikasi Presentasi melalui Penerapan Model Pembelajaran Tutor Sebaya pada Siswa Kelas X OTKP 1 SMK Negeri 2 Tegal Semester Genap Tahun Pelajaran 2017/2018 - Jaenali Jaenali (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2019)
The purpose of this study is to improve the learning achievement of the material Operate the Application Presentation through the application of learning models peer tutors of class X Automation and Office Management (OTKP) 1 Vocational High School 2 Tegal even semester 2017/2018 academic year. This research is in the form of classroom action research, which is a study conducted collaboratively between researchers, students, and teaching teachers in Office Technology subjects. The subjects of this study were class X OTKP 1 Tegal Vocational High School 2 totaling 32 people. The implementation of the action is carried out by the planned researcher together with the peer teacher. The data sources of this research are informants, places, events and documents. Data collection techniques used are observation, testing and documentation techniques. The research process was carried out in two cycles considering the researcher was the teacher of the subject. Each cycle consists of four stages, namely action planning, action implementation, observation and evaluation, and analysis and reflection. Each cycle is conducted in three meetings and each meeting is 4 x 45 minutes. Based on the results of the research conducted, it can be concluded that there was an increase in learning achievement of Office Technology of class X OTKP 1 students at SMK Negeri 2 Tegal through the application of peer tutoring learning models. The results of the research that have been carried out are that there is an increase in student office technology learning achievement from 18 students (56%) who completed the pre-cycle to 24 students (75%) who completed the first cycle and increased to 31 students (97%) who reached the completion limit learn. The average value of knowledge in the first cycle is 75.31, increasing by 4.68 from the average pre-cycle value. While the average value of skills in the first cycle is 79.06, increasing by 7.81 from the average pre-cycle value. The average value of knowledge in the second cycle was 80.78, increasing 5.47 from the average cycle I. While the average value of skills in the second cycle was 86.72, it increased 7.66 from the average value in the first cycle.